Color Cherenkov imaging of clinical radiation therapy - Daniel A. Alexander (Nature Publishing Group, 2021)
A novel three-channel intensified camera capable of imaging Cherenkov emission in full color was developed, allowing for sensitivity to in vivo biological tissue information during radiotherapy.